2019
DOI: 10.1175/jcli-d-18-0601.1
|View full text |Cite
|
Sign up to set email alerts
|

Falling Trend of Western Disturbances in Future Climate Simulations

Abstract: Western disturbances (WDs) are synoptic-scale cyclonic weather systems advected over Pakistan and northern India by the subtropical westerly jet stream. There, they are responsible for most of the winter precipitation, which is crucial for agriculture of the rabi crop as well for as more extreme precipitation events, which can lead to local flooding and avalanches. Despite their importance, there has not yet been an attempt to objectively determine the fate of WDs in future climate GCMs. Here, a tracking algor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 37 publications
4
38
0
Order By: Relevance
“…This increase of 9% in the net flux is much smaller than the apparent contribution from increased humidity alone ( q ′̄ : 28%), which is due to mitigating effects from the dynamics ( q ′ : −20% ). For comparison, we note that Hunt et al (2019) found that WDs were likely to weaken by about 12% in an end-of-century RCP8.5 climate.…”
Section: Future Climatementioning
confidence: 91%
See 1 more Smart Citation
“…This increase of 9% in the net flux is much smaller than the apparent contribution from increased humidity alone ( q ′̄ : 28%), which is due to mitigating effects from the dynamics ( q ′ : −20% ). For comparison, we note that Hunt et al (2019) found that WDs were likely to weaken by about 12% in an end-of-century RCP8.5 climate.…”
Section: Future Climatementioning
confidence: 91%
“…1.2) that proxy techniques are not reliable when it comes to counting WDs, we cannot be certain of the significance of these results in the context of changing WD frequency in a future climate. However, Hunt et al (2019) used a feature-tracking algorithm to detect WDs in the output of 24 CMIP5 models. Compared to a 1980-2005 baseline, they found that 2080-2100 WD frequency decreased significantly by an average 11% and 17% in RCP4.5 and RCP8.5 experiments respectively.…”
Section: Projected Trends Of Western Disturbancesmentioning
confidence: 99%
“…Severe glacial mass loss (−0.437 ± 0.191 m w.e.) since the 1960s corresponds to a further and prominent shift towards drier conditions arising out of the weakening of both the ISM and westerlies (Qin et al, 2000;Hunt et al, 2019;Basistha et al, 2009;Singh et al, 2019;Sano et al, 2012Sano et al, , 2013Sano et al, , 2017. Increasing regional and global temperatures coupled with progressive regional industrialization may have exacerbated the retreat rates.…”
Section: Three Major Phases In the Mass Balance Dynamicsmentioning
confidence: 99%
“…It broadly affected the Asian summer monsoon, and the region has progressively moved towards a drier phase, subsequent to a breakdown in the ITCZ and Northern Hemisphere temperature relation since the mid-19th century (Ridely et al, 2015;Xu et al, 2012). Nevertheless, the strength of the westerlies in the region remained unaffected until the mid-20th century (Joswaik et al, 2013;Hunt et al, 2019;Khan et al, 2019). Thus, depending upon the geographical location and proximity to the oceans, a distinct regionality developed, with a decline in summer monsoon precipitation.…”
Section: Increasing Regional Heterogeneitymentioning
confidence: 99%
See 1 more Smart Citation